THE LINK BETWEEN REPLACEMENT LABOUR AND ERUPTION OF VIOLENCE DURING INDUSTRIAL ACTION - Mlungisi Tenza (Obiter, 2016)
The use of replacement workers during strikes has been a cause for concern in recent years. Since industrial action often becomes violent, the question that arises is whether the use of replacement labour can be one of the factors that contributes to the eruption of such violence. This article investigates whether there is a link between the use of replacement labour and the eruption of violence during a strike. In doing this, the author refers to certain instances where such use has resulted in friction between striking employees and replacement workers. Strikers believe that the use of such workers robs them of their weaponry of strike. The argument goes on to say that such use enables the employer to not commit faithfully to negotiations because he or she does not feel the economic harm that the employees want to inflict, as he or she is able to continue with production or delivery, while the former suffer from the “no work no pay” rule. The article argues that in the presence of the provision in the Labour Relations Act that permits employers to use such workers, the relations between employers and unions will remain unhealthy, if not tense. The article further argues that such use will have the effect of protracting negotiations and delay dispute settlements. As a result, it is suggested that the relevant clause be removed from the Labour Relations Act.